Manajemen Perpustakaan Sekolah Menengah Kejuruan Negeri 2 Kabupaten Musi Rawas - Rhoni Rodin; Hilda Athiya; Tiara Dwi Larasati (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
Introduction. School library management is basically a process of optimizing human, material, and budgetary contributions to achieve library goals. The purpose of this study is to describe the library management of SMKN 2 Musi Rawas, the specific objective is to find out how the implementation of management functions in the library of SMKN 2 Musi Rawas starts from planning (planning), organizing (organizing), implementing (actuating), controlling (controlling) which is applied in the library of SMKN 2 Musi Rawas. Research methods. This research method the author uses a descriptive research method with a qualitative approach to find out how the implementation of library management in the library of SMKN 2 Musi Rawas. The subject of this research is the head of the library, librarians, teachers, students and schools. Results and Discussion. 1) Management planning at the library of SMK Negeri 2 Musi Rawas is to change the management of the library which used to use a conventional/manual system to switch to a digital/automated system. 2) Organizing Library Management at SMK Negeri 2 Musi Rawas has been going well, this is evidenced by the existence of an organizational structure and a clear division of labor. 3) The movement of activities in the library is initiated by the head of the library as a driving model for the existing library staff. 4) related to control, the library of SMK Negeri 2 Musi Rawas carries out an evaluation of the work carried out on a regular basis. Conclusions and suggestions. implementation of library management functions at SMK Negeri 2 Musi Rawas is carried out starting from planning, organizing, implementing, and also controlling and there are also several obstacles faced by libraries in their implementation.